Disordered brownmillerite Ba2InCeO5+delta with enhanced oxygen reduction activity - Jijil, Chamundi P.; Unni, SreeKuttan M.; Sreekumar, Kurungot; Devi, R. Nandini (Chemistry of Materials, 2012)
A disordered brownmillerite, Ba2InCeO5+delta, with slight tetragonal distortion from ideal cubic perovskite is synthesized and its oxygen reduction reactivity tested. The material displayed oxygen reduction behavior in alkaline solution comparable to that of standard 40 wt % Pt/C catalyst and attractive activity characteristics which renders it a potential system for low temperature fuel cell applications.
Keywords: brownmillerite; fuel cell; oxygen reduction reaction; Rietveld refinement